Impact of sudden stratospheric warmings on the neutral density, temperature and wind in the MLT region - Zhou, Baozhu; Yi, Wen; Xue, Xianghui; Ye, Hailun; Zeng, Jie; Li, Guozhu; Tsutsumi, Masaki; Gulbrandsen, Njål; Chen, Tingdi; Dou, Xiankang (Frontiers in Astronomy and Space Sciences, 2023)
In this study, the neutral density and horizontal wind observed by the four meteor radars, as well as the temperature measured by the Microwave Limb Sounder (MLS) onboard the Aura satellite are used to examine the response of neutral density, wind, and temperature in the MLT region to the stratospheric sudden warmings (SSWs) during 2005 to 2021 in the Northern Hemisphere. The four meteor radars include the Svalbard (78.3°N, 16°E) and Tromsø (69.6°N, 19.2°E) meteor radars at high latitudes and the Mohe (53.5°N, 122.3°E) and Beijing (40.3°N, 116.2°E) meteor radars at middle latitudes. The superposed epoch analysis results indicate that: (1) the neutral density over Svalbard and Tromsø at high latitude increased at the beginning of SSWs and decreased after the zonal mean stratospheric temperature reached the maximum. However, the neutral density over Mohe at midlatitudes decreased in neutral density at the beginning of SSW and increase after the zonal mean stratospheric temperature reached the maximum. (2) The zonal wind at high latitudes show a westward enhancement at the beginning of SSWs and then shows an eastward enhancement after the stratospheric temperature reaches maximum. However, the zonal wind at midlatitudes shows an opposite variation to at high latitudes, with an eastward enhancement at the onset and changing to westward enhancements after the stratospheric temperature maximum. The meridional winds at high and midlatitudes show a southward enhancement after the onset of SSW and then show a northward enhancement after the stratospheric temperature maximum. (3) In general, the temperature in the MLT region decreased throughout SSWs. However, as the latitudes decrease, the temperature cooling appears to lag a few days to the higher latitudes, and the degree of cooling will decrease relatively.